2017
DOI: 10.18178/ijke.2017.3.1.079
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study Using StegExpose for Steganalysis

Abstract: Steganography is the art of hiding secret message in innocent digital data files. Steganalysis aims to expose the existence of steganograms. While internet applications and social media has grown tremendously in recent years, the use of social media is increasingly being used by cybercriminals as well as terrorists as a means of command and control communication including taking advantage of steganography for covert communication. In this paper, we investigate open source steganography/steganalysis software an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Along with the high-quality stego image and large HC, the proposed technique strength and robustness against different steganalysis and cracking technique is also analyzed. The proposed technique is tested against different steganalysis attacks using StegExpose [47], StegSecret [48], and Jia-Fa method [49]. The experimental results revealed that the proposed technique is robust against spatial and DCT domain steganalysis attacks.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Along with the high-quality stego image and large HC, the proposed technique strength and robustness against different steganalysis and cracking technique is also analyzed. The proposed technique is tested against different steganalysis attacks using StegExpose [47], StegSecret [48], and Jia-Fa method [49]. The experimental results revealed that the proposed technique is robust against spatial and DCT domain steganalysis attacks.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Penelitian kedua oleh [8] Peneliti ketiga oleh [9] dengan judul "Penerapan Metode Steganalysis untuk Pengembalian Data pada Hard Drive". Penelitian ini bertujuan untuk melakukan steganalysis dan melewati kode keamanan password pada berkas yang sudah dilakukan steganografi dan melakukan pengembalian berkas yang sudah dilakukan steganografi pada hard drive yang sudah di format.…”
Section: Pendahuluanunclassified
“…Peneliti kedua melakukan investigasi pada aplikasi open source steganografi serta melakukan pengujian pada aplikasi StegExpose untuk proses steganalisis. Setelah melakukan investigasi secara komparatif, hasilnya menunjukan bahwa kemampuan dari aplikasi stegExpose sangat terbatas (Olson et al, 2017).…”
Section: Pendahuluanunclassified